Airway obstruction is associated with reduced variability in specific parts of the tidal breathing flow–volume curve in young children. Issue 2 (17th June 2019) - Seppä, Ville-Pekka; Hult, Anton; Gracia-Tabuenca, Javier; Paassilta, Marita; Viik, Jari; Plavec, Davor; Karjalainen, Jussi
Lung function testing in subjects with limited cooperation, such as young children, the elderly or the disabled, is often extremely challenging even when using methods that need a low level of cooperation like impulse oscillometry (IOS). Hence, measurement and analysis of tidal breathing have been studied as an alternative option for conventional lung function methods in detecting airway obstruction. However, attempts to determine clinically useful obstruction-related tidal breathing indices, such as peak points or line fits from the tidal breathing flow–volume (TBFV) curves, have produced very limited outcomes. A more recent approach has focused on looking at the tidal breathing curve variability over time. The tidal breathing indices and the mathematical methods for their quantification analysed in early studies have been diverse; for instance, approximate entropy [1, 2] and noise limit of the flow signal [3], interquartile range of various tidal breathing indices [4, 5], and coefficient of variability of tidal volume [6]. A common finding has been that lower airway obstruction is associated with reduced variability in the tidal breathing pattern. Impedance pneumography recordings during sleep at night show reduced variability in specific parts of the expiratory flow–volume curve in children with recurrent wheeze http://bit.ly/2Wkfap0